Contribution to the knowledge of history of violence in Peru - Garmendia Lorena, Fausto (2016)
This historical research describes all forms of violence occurred in Peru since the beginning of pre-Inca and Inca cultures, conquest of Peru by the Spaniards, viceroyalty period, independence from the Spanish possession, tumultuous Republic history, standing out the internal conflict of years 1980-2000, and ending with the most prevalent forms of violence in Peru of today.